Disease characteristics, treatment patterns, prognosis, outcomes and lymphoma‐related mortality in elderly follicular lymphoma in the United States. (7th April 2015) - Nabhan, Chadi; Byrtek, Michelle; Rai, Ashish; Dawson, Keith; Zhou, Xiaolei; Link, Brian K.; Friedberg, Jonathan W.; Zelenetz, Andrew D.; Maurer, Matthew J.; Cerhan, James R.; Flowers, Christopher R.
Summary Data from the National LymphoCare Study (a prospective, multicentre registry that enrolled follicular lymphoma (FL) patients from 2004 to 2007) were used to determine disease characteristics, treatment patterns, outcomes and prognosis for elderly FL (eFL) patients. Of 2650 FL patients, 209 (8%) were aged >80 years; these eFL patients more commonly had grade 3 disease, less frequently received chemoimmunotherapy and anthracyclines, and had lower response rates when compared to younger patients. With a median follow‐up of 6.9 years, 5‐year overall survival (OS) for eFL patients was 59%; 38% of deaths were lymphoma‐related. No treatment produced superior OS among eFL patients. In multivariate Cox models, anaemia, B‐symptoms and male sex predicted worse OS (P < 0·01); a prognostic index of these factors (0, 1 or ≥2 present) predicted OS [hazard ratio (95% CI): ≥2 vs. 0, 4·72 (2·38–9·33); 1 vs. 0, 2·63 (1·39–4·98)], with a higher concordance index (0·63) versus the Follicular Lymphoma International Prognostic Index (0·55). The index was validated in an independent cohort. In the largest prospective US‐based eFL cohort, no optimal therapy was identified and nearly 40% of deaths were lymphoma‐related, representing baseline outcomes in the modern era.